Perbedaan Tingkat Depresi Antara Guru Yang Mengajar Di Slb Negeri Surakarta Dengan Guru Yang Mengajar Di SMP Negeri 1 Surakarta - Halimah, Fadilatul, Prof. Dr. H. M. Fanani, dr., Sp.KJ (K), dr. Yusuf Alam Romadhon, M.Kes (2016)
Background: Demands work experience on the Extraordinary School's teachers, of course different with the problem on the Junior High School's teachers. Teacher is one profession jobs have a level of depression most of all in the aspects of physical, psychology and job satisfaction. Depression is a disturbance in the mood of the most common happen characterized by a state of stress, loss of pleasure or interest, there's feeling of guilty or self-esteem is low, less until loss of appetite, having sleep disorder, lack of energy, and difficulty concentrating. Objective: this study aims to analyze the existence of difference levels of depression among teachers who teach at SLB Negeri Surakarta with teachers who teach in SMP Negeri 1 Surakarta and frequency distribution of difference levels of depression among teachers who teach at SLB Negeri Surakarta with teachers who teach in SMP Negeri 1 Surakarta. Methods: this research is a study of analytical observational, with the use of cross sectional. Results: based on data of questionnaire BDI on teachers who teach at SLB Negeri Surakarta and teachers who teach in SMP Negeri 1 Surakarta tested using Mann-Whithney, no different at trial was obtained by teachers who teach at SLB Negeri Surakarta with teachers who teach in SMP Negeri 1 Surakarta has the value p = 0,040 (p < 0,05) which means that is a meaningful statistic. Conclusion: there is a difference in the level of depression among teachers that taught at the SLB Negeri of Surakarta with teachers who teach in SMP Negeri 1 Surakarta. The level of depression, owned a teacher who teaches at SLB Negeri Surakarta is higher compared with teachers who teach in SMP Negeri 1 Surakarta. Keywords: Extraordinary School's Teacher, Junior High School's Teacher, Depression